2014
DOI: 10.3389/fpls.2014.00343
|View full text |Cite
|
Sign up to set email alerts
|

Wheat and barley dehydrins under cold, drought, and salinity – what can LEA-II proteins tell us about plant stress response?

Abstract: Dehydrins as a group of late embryogenesis abundant II proteins represent important dehydration-inducible proteins whose accumulation is induced by developmental processes (embryo maturation) as well as by several abiotic stress factors (low temperatures, drought, salinity). In the review, an overview of studies aimed at investigation of dehydrin accumulation patterns at transcript and protein levels as well as their possible functions in common wheat (Triticum aestivum), durum wheat (T. durum), and barley (Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 48 publications
2
90
0
1
Order By: Relevance
“…Dehydrins are group of late embryogenesis-abundant II proteins induced during certain developmental stages and by abiotic stresses (Close 1996;Hanin et al 2011;Kosová et al 2014). Based on the increase of their expression under different drought regimes, two dehydrins genes, HvDHN1 and HvDHN9, were chosen (Choi et al 1999;Suprunova et al 2004;Karami et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrins are group of late embryogenesis-abundant II proteins induced during certain developmental stages and by abiotic stresses (Close 1996;Hanin et al 2011;Kosová et al 2014). Based on the increase of their expression under different drought regimes, two dehydrins genes, HvDHN1 and HvDHN9, were chosen (Choi et al 1999;Suprunova et al 2004;Karami et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They are largely hydrophilic proteins that contain different amounts of K-segments (lysine-rich repeats), S-segments (tract of serine residues), and Ysegments (conserved N-terminal sequence) (Svensson et al, 2002). Dehydrins are often responsive to short-term LT (cold acclimation), vernalization and phenological development (Kosová et al, 2014b). They are localized to the cytoplasm or nucleus, depending on the cell type.…”
Section: Late Embryogenesis-abundant Proteins (Dehydrins)mentioning
confidence: 99%
“…Although barley is comparatively the most tolerant cultivated Triticeae species with respect to dehydrative stresses, particularly drought and salinity, in general it represents less freezing tolerance at the end of cold acclimation phase when compared with wheat cultivars with same growth habits (Kosová et al, 2014b). In spring barley, early maturing can be considered as the basic trait involved in adaptation to the environment.…”
Section: Analysis Of the Barley Proteome Under Lt Stressmentioning
confidence: 99%
“…Temperatures and drought stress pre-treatment factors are associated with plant The values followed by different letters in a column are significantly different at P \ 0.05 according to Duncan's multiple range test (DMRT) cell dehydration. Dehydration stress factors induce profound cellular response aimed at an elimination of water loss (Kosová et al 2014). The experimental results showed that desiccation could increase shoot regeneration of treated calluses derived from the tested barley genotypes, but the increasing efficiency was crucially dependent on the degree of temperature.…”
Section: Effect Of Heat and Nacl On Regenerationmentioning
confidence: 88%